Impact of age‐related macular degeneration in patients with glaucoma: understanding the patients' perspective. (26th January 2016) - Skalicky, Simon E; Fenwick, Eva; Martin, Keith R; Crowston, Jonathan; Goldberg, Ivan; McCluskey, Peter
Abstract: Background: The aim of the study is to measure the impact of age‐related macular degeneration on vision‐related activity limitation and preference‐based status for glaucoma patients. Design: This was a cross‐sectional study. Participants: Two‐hundred glaucoma patients of whom 73 had age‐related macular degeneration were included in the research. Methods: Sociodemographic information, visual field parameters and visual acuity were collected. Age‐related macular degeneration was scored using the Age‐Related Eye Disease Study system. Main Outcome Measures: The Rasch‐analysed Glaucoma Activity Limitation‐9 and the Visual Function Questionnaire Utility Index measured vision‐related activity limitation and preference‐based status, respectively. Regression models determined factors predictive of vision‐related activity limitation and preference‐based status. Differential item functioning compared Glaucoma Activity Limitation‐9 item difficulty for those with and without age‐related macular degeneration. Results: Mean age was 73.7 (±10.1) years. Lower better eye mean deviation ( β : 1.42, 95% confidence interval: 1.24–1.63, P < 0.001) and age‐related macular degeneration ( β : 1.26 95% confidence interval: 1.10–1.44, P = 0.001) were independently associated with worse vision‐related activity limitation. Worse eye visual acuity ( β : 0.978, 95% confidence interval: 0.961–0.996, P = 0.018), high risk age‐related macular degeneration ( β : 0.981, 95% confidence interval: 0.965–0.998, P = 0.028) and severe glaucoma ( β : 0.982, 95% confidence interval: 0.966–0.998, P = 0.032) were independently associated with worse preference‐based status. Glaucoma patients with age‐related macular degeneration found using stairs, walking on uneven ground and judging distances of foot to step/curb significantly more difficult than those without age‐related macular degeneration. Conclusions: Vision‐related activity limitation and preference‐based status are negatively impacted by severe glaucoma and age‐related macular degeneration. Patients with both conditions perceive increased difficulty walking safely compared with patients with glaucoma alone.